Pengaruh pemberian probiotik EM4 terhadap pertumbuhan ikan Lele Sangkuriang (Clarias gariepinus Var) yang dipelihara di kolam terpal - Tania Serezova Augusta (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2017)
The purpose of this study is to determine the rate of growth of Sangkuriang Catfish that kept in tarpaulin pond with the provision of probiotics EM4. This study used a Completely Randomized Design consisting of 3 treatment with 3 replications The treatments used in this study were :Treatment A = Dose EM4 given as much as 15ml/liter of water, Treatment B = Dose EM4 given as much as 10 ml/liter of water and Treatment C = not given EM4. The results of this study showed that better treatment were the treatment of A and B. While for the C treatment slightly inhibited for the growth of Sangkuriang Catfish. Water quality of tarpaulin ponds during the maintenance of Sangkuriang Catfish shows the condition of temperature, DO and pH that could still been tolerated and feasible for the growth of Sangkuriang Catfish. Key words : Sangkuriang Catfish, probiotic EM4, dose, tarpaulin pond, water quality.